Profil Konseling Format Klasikal dalam Mereduksi Prokrastinasi Akademik Siswa SMK Kharismawita 2 - Marisa, Cindy; Utami, Sri; Fitriyanti, Evi (SAP (Susunan Artikel Pendidikan), 2024)
Academic procrastination has a psychological impact on students in the form of negative emotional disturbances in students, such as anxiety and stress. This study aims to measure the effectiveness of classical format counselling guidance (BK) services in reducing students' academic procurement at SMK Kharismawita 2 Jakarta. The study used the experimental method of one group pretest-posttest design with a sample of 45 students in class X selected by purposive sampling. Academic procrastination instruments are used to measure changes in student behaviour. The study results showed an increase in the average score in all aspects after the service was provided. Although the N-Gain value in the category was low (0.3), the paired sample test showed significant changes in all aspects with a significance value of 0.000. Classical information services have been proven effective in increasing students' awareness of academic procrastination. The results of this study provide recommendations for counsellors in schools to utilize classical-based BK services as an intervention strategy in reducing students' overall academic procrastination behaviour.